The Greek-Americans Voice: From an Ethnic to a Political Definition - Stubos, George (Études helléniques / Hellenic Studies, 1998)
This article examines the growth process of the ethnic-organizational structure of Greeks in America. It claims that from the first “local ethno-cultural associations” to the establishment of AHEPA and to the creation of the so called Greek lobby in the 1970’s, there is a linear continuity conforming to the changing needs of the Greek community as well as the changing manner by which the United States incorporates and articulates the interests of its minorities in the decision making profess. Finally, the issues investigated in some depth are the internal and external factors that contributed to the rise of the Greek lobby, defined its functions and determined its limits.